2006
DOI: 10.1038/sj.jcbfm.9600289
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Reference Tissue Models for the Analysis of [11C](R)-PK11195 Studies

Abstract: [ 11 C](R)-PK11195 is a marker of activated microglia, which can be used to measure inflammation in neurologic disorders. The purpose of the present study was to define the optimal reference tissue model based on a comparison with a validated plasma input model and using clinical studies and Monte Carlo simulations. Accuracy and reproducibility of reference tissue models were evaluated using Monte Carlo simulations. The effects of noise and variation in specific binding, nonspecific binding and blood volume we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
99
0

Year Published

2006
2006
2016
2016

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 89 publications
(102 citation statements)
references
References 37 publications
(43 reference statements)
2
99
0
Order By: Relevance
“…A similar interaction may occur for TSPO with any of the 3 proteins that combine with TSPO to form the so-called permeability transition pore (25,26). In addition, the higher specific binding of improved radioligands may increase in vivo sensitivity to the genotype, in contrast to the prototypical agent 11 C-(R)-PK11195 that has a relatively lower signal-to-noise ratio in brain and may lack the sensitivity needed to detect a genetic effect (4,5,7).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A similar interaction may occur for TSPO with any of the 3 proteins that combine with TSPO to form the so-called permeability transition pore (25,26). In addition, the higher specific binding of improved radioligands may increase in vivo sensitivity to the genotype, in contrast to the prototypical agent 11 C-(R)-PK11195 that has a relatively lower signal-to-noise ratio in brain and may lack the sensitivity needed to detect a genetic effect (4,5,7).…”
Section: Discussionmentioning
confidence: 99%
“…However, these radioligands have a relatively low signal-to-noise ratio. For example, the ratio of specific to nonspecific binding of 11 C-(R)-PK11195 in human brain was reported to be only about 0.2-0.5 (4,5). In contrast, some second-generation radioligands for TSPO, such as [methyl-11 C]N-acetyl-N-(2-methoxybenzyl)-2-phenoxy-5-pyridinamine) ( 11 C-PBR28), have a higher in vivo specific signal to TSPO than 11 C-(R)-PK11195.…”
mentioning
confidence: 99%
“…As both physiological description and clinical consequences of [ 11 C]palmitate model choice have previously been discussed in detail [9,11,23,24], the present study focused on the applicability of these models within spatial and temporal limitations of the PET data. To assess how many parameters could be determined from human [ 11 C]palmitate studies, models of different levels of complexity were compared systematically, in each case relating the model to the underlying physiology [25][26][27].…”
Section: Discussionmentioning
confidence: 99%
“…Such washing is not possible for in vivo imaging, and [ 11 C]PK 11195 has relatively low ratios of specific to nonspecific binding. For example, by using reference tissue models, Kropholler et al have reported that the ratio of specific to nonspecific binding of the active enantiomer (R) of [ 11 C]PK 11195 in human brain is only about 0.2 -0.5 (Kropholler et al, 2006).…”
Section: Introductionmentioning
confidence: 99%